Flexural strengthening of RC beams with CFRP grid-reinforced ECC matrix. (1st April 2018) - Yang, Xu; Gao, Wan-Yang; Dai, Jian-Guo; Lu, Zhou-Dao; Yu, Ke-Quan
Abstract: This paper investigates the flexural performance of a series of RC beams externally bonded with carbon fiber-reinforced polymer (CFRP) grid-reinforced engineered cementitious composite (ECC) matrix. A total of 15 RC beams, including three control and twelve strengthened, were prepared and tested. The test variables included the longitudinal reinforcement ratio, the strengthening configurations that consisted of different cementitious matrices (ECC versus epoxy mortar), different installation methods (prefabricated versus cast-in-place), and different stiffness of CFRP grids. The test results showed that ECC is an ideal cementitious matrix for the strengthening applications where FRP grids are used as the external reinforcement. The flexural strengthening configuration using the epoxy adhesive to bond prefabricated CFRP grid-reinforced ECC plate proved to be the most efficient solution. For such configuration, the plate-end debonding can be avoided and the mid-span debonding can be almost suppressed. Flexural capacity analysis was conducted and demonstrated that the plane section assumption is valid and the full strength composite action can be nearly achieved for the strengthening system. The average ratio of the predicted peak loads to the experimental ones of the strengthened RC beams was 1.05.